Respuestas
Respuesta dada por:
0
Resolver.
6x² + 1 = 7
6x² = 7 - 1
6x² = 6
x² = 6/6
x² = 1
x = √1 Tiene 2 soluciones
x = 1 Porque 1 * 1 = 1
o
x = - √1
x = - 1 Porque ( - 1)( - 1) = 1
Solucion.
(1 , - 1)
6x² + 1 = 7
6x² = 7 - 1
6x² = 6
x² = 6/6
x² = 1
x = √1 Tiene 2 soluciones
x = 1 Porque 1 * 1 = 1
o
x = - √1
x = - 1 Porque ( - 1)( - 1) = 1
Solucion.
(1 , - 1)
manuebeltran1:
Gracias
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 9 años
hace 9 años
hace 9 años
hace 10 años
hace 10 años
hace 10 años